103k views
5 votes
Solve the following linear system of equations using substitution.
y = 3x - 5
y = 2x - 6

User Nibbana
by
4.9k points

1 Answer

4 votes

Answer:

x = -1

y = -8

Explanation:

Given

y = 3x - 5

y = 2x - 6

By substitution . Substituting 2x - 6 for y in the first equation, we have

2x - 6 = 3x - 5

Combine like terms

5 - 6 = 3x - 2x

-1 = x

x = -1

Substitute -1 for x in any of the equations to get y.

Using equation 1 ,

We have

y = 3(-1) - 5

y = -3 -5

y = -8

Therefore y = -8 and

x = -1

User Dader
by
5.6k points